Interactions of Digitalisation and Sustainable Finance in Shaping Profitability of Indonesian State Banks - Jonnardi Jonnardi; Dessy Adelin; Muhammad Azizurrohman (Accounting Department, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jawa Timur, 2025)
Purpose: This study examines the determinants of financial performance in Indonesian state-owned and regionally owned banks by integrating prudential indicators with developmental, sustainability, and digital transformation variables. It evaluates how digital capability and green lending moderate the effects of credit risk, earning power, and developmental credit on profitability. Method: The analysis uses balanced panel data from six banks over two thousand nineteen to two thousand twenty-three. A fixed effect panel regression model with interaction terms captures both direct determinants and moderating influences. Key predictors include nonperforming loans, net interest margin, developmental credit, and cooperative or village enterprise lending, while moderating variables comprise digital capability and green lending. Findings: Nonperforming loans exert the strongest negative effect on profitability, whereas net interest margin remains the primary driver of return on assets. Developmental credit and lending to local enterprises enhance financial performance. Green lending and environmental, social, and governance performance are positively associated with profitability. Digital capability weakens the adverse influence of credit risk and strengthens the gains from earning power. Green lending amplifies the positive effect of developmental credit. Implications: Profitability in state-aligned banks reflects the combined influence of prudential fundamentals, developmental mandates, sustainable finance initiatives, and digital transformation. Strengthening credit risk management, improving developmental programme mechanisms, expanding green finance, and deepening digital capability are essential for enhancing performance and informing regulatory incentive design. Novelty/Value: This study offers integrated empirical evidence on prudential, developmental, sustainability, and digital determinants of profitability in Indonesian state banking. It demonstrates that digital capability and green lending not only improve financial outcomes but also reinforce the effectiveness of developmental credit, thereby advancing research on development-oriented and sustainable finance models.